2008
DOI: 10.1007/s00213-008-1257-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide modulates the discharge rate of basal forebrain neurons

Abstract: NO modulates the BF neuronal discharge rates in a dose-dependent manner. The inhibitory effect is partly mediated via adenosine A1 receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 60 publications
3
27
0
Order By: Relevance
“…Although the drugs used in these studies may act in the peripheral vasculature, central effects on cholinergic DBB neurons are also possible. Actually, effective triggering of migraine-like headaches can be achieved by nitric oxide donors’ infusion, which has been shown to alter DBB cholinergic neuronal activity (Kostin et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Although the drugs used in these studies may act in the peripheral vasculature, central effects on cholinergic DBB neurons are also possible. Actually, effective triggering of migraine-like headaches can be achieved by nitric oxide donors’ infusion, which has been shown to alter DBB cholinergic neuronal activity (Kostin et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…This response was more prominent in stimulus-on than in stimulus-off neurons and the inhibitory effect is partly mediated via purinergic or metabotropic glutamate receptors (22,23,32). Although the rationale for attenuated urinary sodium excretion observed after icv insulin administration in animals simultaneously treated with L-NAME remains unknown, speculatively, it is tempting to suggest that perhaps one of the efferent signals triggered by insulin in the CNS may be nitrergic in nature.…”
Section: Discussionmentioning
confidence: 85%
“…These effects might be partially due to a direct inhibition of growth factors by S-nitrosylation (21). Also, recent studies have demonstrated that NO modulates the synaptic activity and neuronal discharge rates in a dose-dependent manner (22,23). However, there is little information on the neural mechanisms that mediate the effects of icv insulin administration on renal sodium handling in rats.…”
Section: Introductionmentioning
confidence: 94%
“…The details of the surgical and recording procedures have been described earlier (Kostin et al, 2008). Briefly, eleven rats were anesthetized by urethane (i.p., 1.5g/kg) and placed in a stereotaxic apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…NO levels are higher in the cortex during spontaneous arousal and in the basal forebrain (BF) during sleep deprivation (SD) (Burlet and Cespuglio, 1997, Cespuglio et al, 2004, Kalinchuk et al, 2006a). Recent electrophysiological studies show that locally increased NO concentration predominantly exerts inhibitory effects on the discharge of BF neurons (Kostin et al, 2008, Kostin et al, 2009). Such inhibition is proposed to induce the compensatory recovery sleep after prolonged waking, since blockade of NO synthesis in the BF impairs recovery sleep subsequent to SD (Kalinchuk et al, 2006a, Kalinchuk et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%